Reconsidering the Cut Score of Korean National Medical Licensing Examination - Duck Sun Ahn; Sowon Ahn (Journal of Educational Evaluation for Health Professions, 2007)
After briefly reviewing theories of standard setting we analyzed the problems of the current cut scores. Then, we reported the results of need assessment on the standard setting among medical educators and psychometricians. Analyses of the standard setting methods of developed countries were reported as well. Based on these findings, we suggested the Bookmark and the modified Angoff methods as alternative methods for setting standard. Possible problems and challenges were discussed when these methods were applied to the National Medical Licensing Examination.